2011
DOI: 10.1073/pnas.1018845108
|View full text |Cite
|
Sign up to set email alerts
|

A sequential mechanism for clathrin cage disassembly by 70-kDa heat-shock cognate protein (Hsc70) and auxilin

Abstract: An essential stage in endocytic coated vesicle recycling is the dissociation of clathrin from the vesicle coat by the molecular chaperone, 70-kDa heat-shock cognate protein (Hsc70), and the J-domain-containing protein, auxilin, in an ATP-dependent process. We present a detailed mechanistic analysis of clathrin disassembly catalyzed by Hsc70 and auxilin, using loss of perpendicular light scattering to monitor the process. We report that a single auxilin per clathrin triskelion is required for maximal rate of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 33 publications
4
53
1
Order By: Relevance
“…ATP hydrolysis by Hsc70 bound in this region potentially could alter triskelion pucker and put strain on the lattice to cause the destabilization suggested by in silico models. The issue of how many ATPs must be hydrolyzed to induce disassembly and the precise sequence of molecular interactions during uncoating is not resolved (Bocking et al 2011, Rothnie et al 2011. Three studies have also suggested a role for CLC in uncoating through independent influence on hsc70 and auxillin activity (DeLuca-Flaherty et al 1990, Ferreira et al 2012, Schmid et al 1984, though uncoating CHC17 can occur without CLC (Ungewickell et al 1995).…”
Section: Biochemistry Of Clathrin Assembly Disassembly and Nanomatementioning
confidence: 99%
“…ATP hydrolysis by Hsc70 bound in this region potentially could alter triskelion pucker and put strain on the lattice to cause the destabilization suggested by in silico models. The issue of how many ATPs must be hydrolyzed to induce disassembly and the precise sequence of molecular interactions during uncoating is not resolved (Bocking et al 2011, Rothnie et al 2011. Three studies have also suggested a role for CLC in uncoating through independent influence on hsc70 and auxillin activity (DeLuca-Flaherty et al 1990, Ferreira et al 2012, Schmid et al 1984, though uncoating CHC17 can occur without CLC (Ungewickell et al 1995).…”
Section: Biochemistry Of Clathrin Assembly Disassembly and Nanomatementioning
confidence: 99%
“…Recent structural [47,48] and biophysical studies [49] have further elucidated the role of auxilin in coat disassembly. Auxilin binds directly to both clathrin and the uncoating ATPase, Hsc70.…”
Section: Introductionmentioning
confidence: 99%
“…Clathrin coat disassembly has been reported as the appearance of clathrin triskelia in the supernatant fraction of a high speed centrifugation of fractionated brain homogenates, although baskets remain in the pellet (9,23). Disassembly of neuronal clathrin coats has also been observed by measuring changes in average light scattering as a function of Hsc70 ATPase activity (24,25). Recent work has suggested a cooperative disassembly model based on total internal reflection fluorescence microscopy measurements with tethered neuronal clathrin baskets reconstituted from purified components (20).…”
mentioning
confidence: 99%